Generation of Different Steps Shaft on CNC Lathe Utilizing G-Code Programming (Texas Journal of Engineering and Technology, 2023)
Different kind of parts can be machined on the CNC machine utilizing g- code as the programming dialect. The TPS3910 preparing machine arrangement were obtained for commonsense works out within the CNC research facility to improve student’s information of CNC parts programming. The paper profiles the strategies for creating a four step shaft on lathe utilizing g-code programming. Plastic work piece of 70mm in length and 20mm distance across was utilized as the clear since as it were nonmetallic fabric can be machined on the preparing machine gear. The required parameters required for the programming are the measurements of the shaft to be created. After the set-up of the machine, vital information for x, y, and z facilitates were decided. The program was run on recreation mode some time recently machining mode to anticipate any mistake amid the real machining operation. The result approves CNC machining operation tall dimensional exactness and nonattendance of blunder utilizing g-code programming.